Biomimetic and Biohybrid Systems : 4th International Conference, Living Machines 2015, Barcelona, Spain, July 28 - 31, 2015, Proceedings - Wilson, Stuart P.; Verschure, Paul F.M.J.; Mura, Anna.; Prescott, Tony J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the proceedings of the 4th International Conference on Biomimetic and Biohybrid Systems, Living Machines 2015, held in Barcelona, Spain, in July 2015. The 34 full and 13 short papers presented in this volume were carefully reviewed and selected from 50 submissions. The themes they deal with are: locomotion, particularly for soft-bodies; novel sensing and autonomous control systems; and cognitive architectures, social robots, and human-robot interaction.
Keywords: Artificial intelligence; Computer vision; Information theory; Data mining; Artificial Intelligence; Computer Imaging, Vision, Pattern Recognition and Graphics; Theory of Computation; Data Mining and Knowledge Discovery